Impacts of the Triple Global Crisis on Growth and Poverty : The Case of Yemen - Breisinger, Clemens; Diao, Xinshen; Collion, Marie-Helen; Rondot, Pierre (2012)
Yemen is an oil-exporting and food-importing country with the highest levels of poverty in the Middle East and North Africa. The impacts of the triple crisis are likely to further complicate pre-existing conditions of conflict, oil depletion and governance failure. Using a dynamic CGE model, this article finds that oil-driven growth in 2008 dominated the negative growth impacts of the food crisis, but that growth was not pro-poor. The financial crisis of 2009 slowed growth sharply and raised the poverty rate to 42.8%, up from 34.8% in 2005/6. Poverty continues to be higher in rural areas, where almost half the population live in poverty.